2021
DOI: 10.4103/jfmpc.jfmpc_2293_20
|View full text |Cite
|
Sign up to set email alerts
|

Role of immature platelet fraction (IPF) in sepsis patients

Abstract: Sepsis is extremely common amongst critically ill patients and requires early diagnosis. Hence, identifying a biomarker that could acknowledge sepsis at its prior stage is of vital significance. Immature platelets are a percentage of circulating platelets that contain RNA and is a newer parameter that is measured using automated hematology analyzers in diagnosing sepsis. This review article discusses 10 articles that reveal the role of immature platelet fraction in predicting the onset of sepsis and its relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…It increases when platelet production rises and decreases when production falls. A recent systematic review showed that IPF is a reliable biomarker for sepsis diagnosis and prognosis, in terms of severity and mortality [134]. Indeed, it tends to increase before the onset of sepsis and correlates with the scores conventionally used for assessing the severity of sepsis, such as the SOFA score.…”
Section: Immature Platelet Fractionmentioning
confidence: 99%
“…It increases when platelet production rises and decreases when production falls. A recent systematic review showed that IPF is a reliable biomarker for sepsis diagnosis and prognosis, in terms of severity and mortality [134]. Indeed, it tends to increase before the onset of sepsis and correlates with the scores conventionally used for assessing the severity of sepsis, such as the SOFA score.…”
Section: Immature Platelet Fractionmentioning
confidence: 99%
“…On the other hand, caution is advised for this interpretation, as platelets are destroyed and IPF% is subsequently increased in patients with sepsis, regardless of the treatment with chemotherapy 16 , 24 , 25 . In this sense IPF% has been proposed as a biomarker for the prediction of sepsis diagnosis and severity 26 28 .…”
Section: Discussionmentioning
confidence: 99%
“…However, there is contradictory literature on whether there are significant differences between patients with different sepsis severities. 82,83 The mechanisms governing changes in the age profile of platelets in pathological conditions remain unknown, however in many cases they may be associated with an enhanced clearance of platelets leading to increased haematopoiesis. Given such dysregulations in the platelet production process, it is unclear as to whether the platelets produced under these stress conditions are 'normal' and they may perhaps be more akin to those found in animal models of acute platelet depletion.…”
Section: Significance Of Altered Platelet Turnover In Diseasementioning
confidence: 99%